2022
DOI: 10.3390/vetsci9020083
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira interrogans Serogroup Pomona in a Dairy Cattle Farm in a Multi-Host Zootechnical System

Abstract: Bovine leptospirosis is an infectious zoonotic disease causing reproductive problems and economic losses in livestock. This work reports, for the first time in Sicily (South Italy), an outbreak of Leptospira interrogans serogroup Pomona that occurred in cattle farms within the Nebrodi Park and was mainly characterized by full-term abortion. Blood and urine samples were collected at different time points from animals of six different farms (Farms A–F) sharing the same grazing area. Research of antibodies agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Unexpectedly, positivity for serogroups reported to be the most frequently involved in feline leptospirosis in Europe, according to the European consensus statement on leptospirosis, such as Canicola, Grippotyphosa, Sejroe and Icterohaemorrhagiae [ 1 , 2 ], was not detected. Antibodies against the serovars Poi, Arborea, and Mini were never reported before in cats; however, the most frequent seroreactivity found in the present study involved serovars previously described in other hosts in Italy, such as wild boars [ 59 ], pigs [ 60 , 61 ], wolves [ 62 ], Hystrix cristata [ 56 ], horses [ 52 , 55 ], dairy cattle [ 54 ] and wild ruminants [ 51 ], kennel dogs [ 42 , 43 , 46 ] and humans [ 50 ]. Moreover, Tagliabue et al [ 43 ] reported in various host species, antibody-positivity against serogroups Australis (dogs, wild boars, horses, hares, swine, foxes and rodents), Sejroe (cattle, sheep, goats and buffaloes), Icterohaemorrhagiae (dogs, goats and foxes), Pomona (swine, cattle and wild species) and Grippotyphosa (hares).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Unexpectedly, positivity for serogroups reported to be the most frequently involved in feline leptospirosis in Europe, according to the European consensus statement on leptospirosis, such as Canicola, Grippotyphosa, Sejroe and Icterohaemorrhagiae [ 1 , 2 ], was not detected. Antibodies against the serovars Poi, Arborea, and Mini were never reported before in cats; however, the most frequent seroreactivity found in the present study involved serovars previously described in other hosts in Italy, such as wild boars [ 59 ], pigs [ 60 , 61 ], wolves [ 62 ], Hystrix cristata [ 56 ], horses [ 52 , 55 ], dairy cattle [ 54 ] and wild ruminants [ 51 ], kennel dogs [ 42 , 43 , 46 ] and humans [ 50 ]. Moreover, Tagliabue et al [ 43 ] reported in various host species, antibody-positivity against serogroups Australis (dogs, wild boars, horses, hares, swine, foxes and rodents), Sejroe (cattle, sheep, goats and buffaloes), Icterohaemorrhagiae (dogs, goats and foxes), Pomona (swine, cattle and wild species) and Grippotyphosa (hares).…”
Section: Discussionsupporting
confidence: 43%
“…Although in Italy, cases of leptospirosis are widely reported in dogs [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ] and humans [ 47 , 48 , 49 , 50 ] and Leptospira spp. infection has been reported in other host species [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], only one study so far has investigated Leptospira spp. prevalence in cats [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNA was extracted from 0.2 mL of blood or homogenized kidney or resuspended pellet from urines. Lysozyme 10 mg/mL (Roche, Basel, Switzerland) was added to each sample and incubated at 37 °C for 30 min as previously described [ 28 ]. DNA extraction was carried out using the PureLink Genomic DNA kit (Invitrogen, Paisley, UK), according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Pomona is incidental in ruminants and associated with an acute disease, whereas the serogroup Pomona serovar Pomona was frequently reported seropositive in cattle, buffaloes, pigs, and dogs in Thailand [ 10 , 11 ]. In addition, the serovar Pomona had been reported to cause acute and severe leptospirosis in cattle by incidental infection [ 12 , 13 ], especially in multi-host ecologically systems as in Thai rural agriculture areas [ 41 ]. Therefore, the hamster model for acute leptospirosis against heterologous L. interrogans serovar Pomona was set to evaluate vaccine candidate proficiencies of two LRR proteins cloned from L. borgpetersenii serogroup Sejroe.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, serogroup/serovars prevalence in MAT-positive in cattle, buffaloes, and pigs in Thailand were Sejroe, Ranarum, Mini, Pomona, and Bataviae in cattle; Mini, Sejroe, Bratislava, Pomona, and Ranarum in buffaloes; Ranarum, Pomona, Bratislava, and Bataviae in pigs [ 10 ]; and serogroups Icterohaemorrhagiae, Canicola, Pomona, Bataviae and Sejroe in dogs [ 10 , 11 ]. The serogroup Pomona serovar Pomona had been reported to cause acute and severe leptospirosis in cattle by incidental infection [ 12 , 13 ] even though protective immunity against the acute disease caused by L. interrogans serovar Pomona was observed, stimulated by LRR proteins cloned from L. borgpetersenii serogroup Sejroe, the most prevalent leptospiral serovar in bovine livestock in Thailand and South-East Asia.…”
Section: Introductionmentioning
confidence: 99%